Construction and Application of a Learning Resource Sharing Platform in Higher Education Based on Mobile Interactive Technology - Chen, Hui; Shang, Yan (International Journal of Interactive Mobile Technologies (iJIM), 2026)
Driven by the dual forces of digital transformation and the demand for educational equity, the need for cross-temporal and spatial accessibility as well as personalized adaptability of learning resources in higher education has become increasingly urgent. The widespread adoption of mobile technology provides the core hardware support for this demand. However, existing learning resource-sharing platforms face three major challenges: a lack of recommendation accuracy, fragmented knowledge structure relationships, and weak adaptability to mobile interactive scenarios. To address these issues, this paper proposes a knowledge-aware content recommendation method that integrates mobile human-computer interaction features. A knowledge-aware deep learning network with an attention mechanism is constructed, and a mobile platform for sharing learning resources in higher education is developed based on this method. The core innovations are as follows: First, by integrating multimodal mobile interaction features and educational knowledge graphs, a “behavior-knowledge” dual-dimensional user demand modeling system is established, breaking the limitation of traditional recommendation systems that rely solely on behavioral data. Second, a hierarchical attention mechanism is introduced to accurately capture the dynamic associative weights between users and knowledge points, as well as resources and knowledge points, thus addressing the issue of coarse correlation modeling in traditional knowledge-aware recommendations. Third, a lightweight inference architecture is designed to ensure recommendation accuracy while adapting to the computational constraints of mobile terminals. The research results provide a technical paradigm for the precise sharing of mobile learning resources in higher education and are of significant importance for promoting educational resource equity and the construction of personalized learning ecosystems.